Etika Menuntut Ilmu Menurut Kitab Ta’lim Muta’alim - Faridah, Eva (Interdisciplinary Explorations in Research Journal, 2023)
This paper discusses the ethics of studying according to the book Ta'lim al-Muta'alim by Sheikh al- Zarnuzi. This paper focuses on the description of the conceptions and steps that must be taken by students in demanding knowledge. The data sources in this article are obtained from the book Ta'lim al-Muta'alim by Sheikh al-Zarnuzi and several secondary sources in the form of supporting and comparative references that are in accordance with the theme of the article. This paper is a library research using a qualitative approach, which seeks to describe a variable, symptom or situation "as is", and is not intended to test certain hypotheses. The results of this paper show that the ethics of studying in the book of Ta'lim al-Muta'alim are 1) Have a real intention in learning; 2) Smart in choosing teachers, knowledge, friends, and have fortitude in learning; 3) Respect knowledge and scholars; 4) have sincerity, continuity and have a strong interest; 5) Orderly; 6) Tawakal; 7) Smart utilization of learning time; 8) Compassion for fellow knowledge seekers; 9) can take lessons from everything learned: 10) Wara' by keeping away from the shubhat and haram during the study period. From the conception of the ethics of studying, it will give birth to an educational model that prioritizes morals not only oriented to knowledge and skills.   Tulisan ini membahas etika menuntut ilmu menurut kitab Ta’lim al-Muta’alim karya dari Syekh al- Zarnuzi. Tulisan ini memfokuskan kajiannya pada deskripsi-konsepsi serta langkah-langkah yang harus dilakukan peserta didik dalam menuntut ilmu. Sumber data dalam artikel ini diperoleh dari kitab Ta’lim al-Muta’alim karya dari Syekh al-Zarnuzi dan beberapa sumber sekunder berupa referensi- referensi pendukung dan pembanding yang sesuai dengan tema artikel. Tulisan ini adalah penelitian kepustakaan (library research) dengan menggunakan pendekatan kualitatif, yaitu berusaha untuk menggambarkan tentang suatu variable, gejala atau keadaan “apa adanya”, dan tidak dimaksudkan untuk menguji hipotesis tertentu. Hasil dari tulisan ini memperlihatkan bahwa etika menuntut ilmu peserta didik dalam kitab Ta’lim al-Muta’alim adalah 1) Memiliki niat yang sungguh dalam belajar; 2) Cerdas dalam memilih Guru, ilmu, teman, dan memiliki Ketabahan dalam Belajar; 3) Menghormati ilmu dan ulama; 4) memiliki kesungguhan, kontinuitas dan memiliki minat yang kuat; 5) Tertib; 6) Tawakal; 7) Pintar memanfaatkan waktu belajar; 8) Kasih sayang kepada sesama para penuntut ilmu; 9) dapat mengambil hikmah dari setiap yang dipelajari: 10) Wara’ dengan menjaga diri dari yang syubhat dan haram pada masa belajar. Dari konsepsi etika menuntut ilmu ini, akan melahirkan sebuah model pendidikan yang lebih mengedepankan moral tidak hanya terorientasi pada pengetahuan dan keterampilan.